Basal Cell Carcinoma of the Penis: A Case Report and Review of the Literature. (14th September 2014) - Roewe, R. J.; Uhlman, Matthew A.; Bockholt, Nathan A.; Gupta, Amit
Abstract : Basal cell carcinoma of the penis is an extremely rare entity, accounting for less than 0.03% of all basal cell carcinomas. Fortunately, wide local excision of such lesions is generally curative. Fewer than 25 cases have been reported in the literature describing penile basal cell carcinoma. Here we report a case of penile basal cell carcinoma cured with wide local excision.